Microbiological contaminants in cosmetics – isolation and characterization - Budecka, Angela; Kunicka-Styczyńska, Alina (Wydawnictwo Politechniki Łódzkiej, 2014)
Cosmetic industries are not obliged to produce sterile cosmetics. Nevertheless, they are liable to assure safety of the product to the potential consumer. The purpose of the study was isolation and identification of microorganisms with the ability to survive and develop in cosmetics. Five cosmetics applied for facial skin and one cosmetic for body care were tested for the presence of contaminating microbiota. Eight microbial strains were isolated from three cosmetics, from which seven were derived from cosmetic applied on the facial skin. One strain was isolated from body care cosmetic. The recovered microbial strains were characterized and identified to the species level as Pseudomonas aeruginosa, Serratia liquefaciens and Candida parapsilosis. The isolates were opportunistic pathogens and may cause skin irritation and infections, especially via wounded epithelium in immunocompromised consumers. Moreover, due to application area, they pose a health risk to the consumer due to easy access to the eye area as well as nasal and oral cavities through usage of cosmetic preparation.
Keywords: cosmetics; microbiological contamination; Pseudomonas; Serratia; Candida; kosmetyki; skażenie mikrobiologiczne